Obstetrics performance of women with prolonged inter-pregnancy interval (i-pi): a comparative cross-sectional study - Rosli, Anizah Aishah (2015)

(untitled)
BACKGROUND: The inter-pregnancy interval (I-PI) has been reported to influence the outcome of pregnancy and birth. This study was to evaluate the associated factors of I-PI and the impact of I-PI on maternal and fetal outcomes. OBJECTIVE: To determine whether prolonged inter-pregnancy interval (I-PI ≥ 60 months) is associated with higher incidence of adverse obstetrics outcomes, namely labour dystocia, pre-eclampsia, post-partum haemorrhage and fetal outcome such as prematurity compared to inter-pregnancy interval 18-59 months. METHODS: A 12 months prospective cross-sectional study in HUSM from 1st March 2013 to 28th February 2014 was conducted. The study group consisted of pregnant women, with inter-pregnancy interval more than 60 months and the control group consisted of pregnant women, with inter-pregnancy interval between 18 to 60 months. Both the study and control group were screened and selected according to the study’s criteria. There were a total of 272 patients recruited in the duration of the study, with equal number of 126 patients in each arm. Univariate and multivariate logistic regression analysis was used to estimate odds ratio and 95% confidence interval for risk of inter-pregnancy interval such as labour dystocia, pre-eclampsia, postpartum haemorrhage and prematurity. RESULTS: Women with prolonged inter-pregnancy interval (I-PI ≥ 60 months) were more likely to have labour dystocia (OR 1.92, 95% CI 1.09, 3.38; adjusted OR 1.86, 95% CI 1.03, 3.38; p=0.049) as compared to control group. Higher association of prolonged I-PI ≥ 60 months with pre-eclampsia (p=0.049) and primary postpartum haemorrhage (p=0.039). However, there were less number of prematurity (p=0.455) seen among the study group. Advance maternal age was significantly noted to have direct association with prolonged I-PI, labour dystocia, pre-eclampsia and primary postpartum haemorrhage. CONCLUSION: A prolonged inter-pregnancy interval (I-PI ≥ 60 months) is associated with adverse pregnancy and maternal outcome namely labour dystocia, pre-eclampsia and primary postpartum haemorrhage. The results of this study show an association of prolonged I-PI with adverse pregnancy and maternal outcome.